PENGARUH BRAND TRUST, BRAND IMAGE DAN KUALITAS LAYANAN TERHADAP KEPUTUSAN PEMBELIAN (STUDI PADA PELANGGAN MIE GACOAN DI KOTA SIDOARJO) - Diva Maharani Putri; Mas Oetarjo; Misti Hariasih (MANAJEMEN DEWANTARA, 2025)
This study aims to determine the influence of Brand Trust, Brand Image and Sercive Quality on the Purchasing Decision of Mie Gacoan customers in Sidoarjo City. The approach used is quantitative with descriptive methods. The population in this study includes all customers who have purchased Mie Gacoan in the Sidoarjo City area. The sampling technique was carried out using the Non-Probability Sampling Technique with a Purposive Sampling approach, so that a sample of 100 respondents was obtained. The data for this study were collacted using a questionnaire distributed through Google Form. The data obtained will be analysed using the Partial Least Square (PLS) method with the help of SmartPLS 3.0 software. The results of this study found that Brand trust influences the purchasing decision of Mie Gacoan customers in Sidoarjo City, Brand image influences the purchasing decision of Mie Gacoan customers in Sidoarjo City, Service quality influences the purchasing decision of Mie Gacoan customers in Sidoarjo City.